The Utilization of Interactive Multimedia in Improving Vocabulary Knowledge of High School Students - Arifuddin Fathoni; Leo Agung S; Sri Sumaryati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
In the current digital era, English education is becoming increasingly important. By integrating English language learning with digital learning media, it is hoped to create a more dynamic and student-centered learning environment. The goal is to facilitate students in achieving the set learning objectives. This research focuses on evaluating the effectiveness of interactive multimedia in improving English vocabulary comprehension in English subjects at the junior high school level. The research method employed is an experiment with a quasi-experimental design, involving pre and posttests in both control and experimental classes. The sample consists of 32 students from class VIII B (experimental group) and 32 students from class VIII C (control group) in SMPN 1 Jatisrono, selected using cluster random sampling from various classes. The experimental group receives treatment through learning activities using interactive multimedia, while the control group does not use interactive multimedia in the learning process. Data collection is conducted through attitude scale questionnaires filled out by junior high school students. The research findings indicate that the use of interactive multimedia significantly influences the improvement of students' English vocabulary comprehension. This is evidenced by the significant increase in students' English vocabulary knowledge after undergoing learning with interactive multimedia. Interactive multimedia is considered effective in influencing students' comprehension and helping them achieve learning objectives. Thus, interactive multimedia can be considered a suitable learning medium for English subjects at the junior high school level. The use of technology in such learning is crucial to keep up with the times and ensure that students have skills relevant to current global needs. This underscores the importance of integrating technology into education to create more effective and engaging learning experiences for students.